Teasing Apart Overclaiming, Overconfidence, and Socially Desirable Responding. (April 2019) - Bensch, Doreen; Paulhus, Delroy L.; Stankov, Lazar; Ziegler, Matthias
Contamination with positivity bias is a potential problem in virtually all areas of psychological assessment. To determine the impact of positivity bias, one common approach is to embed special indicators within one's assessment battery. Such tools range from social desirability scales to overconfidence measures to the so-called overclaiming technique. Despite the large literature on these different approaches and underlying theoretical notions, little is known about the overall nomological network—in particular, the degree to which these constructs overlap. To this end, a broad spectrum of positivity bias detection tools was administered in low-stakes settings ( N = 798) along with measures of the Big Five, grandiose narcissism, and cognitive ability. Exploratory factor analyses revealed six first-order and two second-order factors. Overclaiming was not loaded by any of the six first-order factors and overconfidence was not explained by either of the two second-order factors. All other measures were confounded with personality and/or cognitive ability. Based on our findings, overclaiming is the most distinct potential indicator of positivity bias and independent of known personality measures.